Using Cooperative Teams-Game-Tournament in 11 Religious School to Improve Mathematics Understanding and Communication - Arsaythamby Veloo; Ruzlan Md-Ali; Sitie Chairany (UUM Press, 2016)
Purpose â€" This paper was part of a larger study which looked into the effect of implementing Cooperative Teams-Games-Tournament (TGT) on understanding of and communication in mathematics. The study had identified the main and interaction effect of using Cooperative TGT for learning mathematics in religious secondary school classrooms. A recommendation was made to incorporate Cooperative TGT as a pedagogical approach to enhance interest in actively learning mathematics with peers via tournaments among students. Students in Cooperative TGT classrooms had also learned to socialise while learning mathematics. Methodology â€" A quantitative approach using Randomized Pretest-Posttest Control Group design was utilised in framing the research study. Data from control groups without TGT treatment was collected using pretest, posttest-1 and posttest-2 across three time periods. The duration between one test and the subsequent test was five weeks. Mathematics understanding and communication was measured using an openended test. A mixed between-within subjects ANOVA was conducted to analyse the effectiveness of Cooperative TGT on understanding of and communication in mathematics. Findings â€" The findings showed that there was significant interaction between group types (experiemental & control groups) and time periods [pretest, posttest-1, & posttest-2 (without TGT)]. Cooperative TGT was found to have an effect on student understanding of and communication in mathematics. The gap score for posttest-1 between understanding of mathematics and communication in mathematics was 17.69, indicating a significant effect of Cooperative TGT on the latter compared to the former. Significance â€" Cooperatiave TGT had encouraged students and teachers to be innovative and creative in the process of teaching and learning of mathematics in classrooms. This study has provided insights into how the teaching and learning of mathematics which incorporated group activities and tournaments in classrooms has helped to improve the understanding of mathematics and communication in mathematics of students at the Madrasah Aliyah, Riau, Indonesia.